Phenotypic Characterization of Sulfolobus islandicus Strains Lacking the B-Family DNA Polymerases PolB2 and PolB3 Individually and in Combination - Bohall, Peter B.; Bell, Stephen D. (Frontiers in Microbiology, 2021)
Across the three domains of life, B-family DNA polymerases play a variety of roles in both DNA repair and DNA replication processes. We examine the phenotypic consequences of loss of the putative repair polymerases PolB2 and/or PolB3 in the crenarchaeon Sulfolobus islandicus. We detect a modest growth advantage when cells lacking the polymerase are grown in unperturbed conditions. Further, we observe a striking insensitivity of the mutant lines to acute treatment with the oxidizing agent, hydrogen peroxide. In addition, cells lacking PolB3 show enhanced sensitivity to the DNA damaging agent 4-NQO. Our data therefore suggest that these non-essential DNA polymerases may influence DNA repair pathway choice in these hyperthermophilic aerobes.